Pengaruh Mekanisme Good Corporate Governance terhadap Financial Statement Fraud dengan Audit Quality sebagai Variabel Moderasi pada Badan Usaha Milik Negara (BUMN) yang Terdaftar di BEI Periode 2020–2024 - Sherina, Sherina; Fadjar, Achmad (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
Financial statement fraud is an act that can undermine the trust of shareholders and stakeholders in a company. Therefore, the implementation of Good Corporate Governance is necessary as a supervisory mechanism to minimize the likelihood of financial statement fraud. This study aims to analyze the influence of the Board of Commissioners (X1), the Audit Committee (X2), and Institutional Ownership (X3) on Financial Statement Fraud (Y), with Audit Quality (Z) as a moderating variable, in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange for the 2020–2024 period. Financial statement fraud is measured using the Beneish M-Score, while audit quality is measured based on the categories of Big Four and non-Big Four public accounting firms. This study employs a quantitative method using secondary data obtained from annual reports, audited financial statements, and corporate governance reports. The research sample was determined using purposive sampling, comprising 95 observations. Data analysis was conducted using panel data regression with the Random Effects Model and Moderated Regression Analysis (MRA) with the assistance of the EViews 12 software. The results indicate that the Board of Commissioners, the Audit Committee, and Institutional Ownership have a significant negative effect on Financial Statement Fraud. Furthermore, Audit Quality amplifies the negative effect of the Board of Commissioners, the Audit Committee, and Institutional Ownership on Financial Statement Fraud. In practical terms, this study contributes to state-owned enterprises by strengthening the implementation of good corporate governance and improving audit quality as a means of preventing financial statement fraud and enhancing corporate transparency and accountability.